2018
DOI: 10.1103/revmodphys.90.011001
|View full text |Cite
|
Sign up to set email alerts
|

Colloquium : High pressure and road to room temperature superconductivity

Abstract: High pressure serves as a path finding tool towards novel structures, including those with very high Tc. The superconductivity in sulfur hydrides with record value of Tc =203 K (!) is caused by the phonon mechanism. However, the picture differs from the conventional one in important ways. The phonon spectrum in sulfur hydride is both broad and has a complex structure. High value of T c is mainly due to strong coupling to the high-frequency optical modes, although the acoustic phonons also make a noticeable con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
103
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(109 citation statements)
references
References 91 publications
4
103
1
1
Order By: Relevance
“…Different states of electronic quantum matter are often tightly linked to lattice degrees of freedom. Examples include superconductivity, periodic lattice distortions and charge-density waves (CDWs), metal-insulator transitions, and nematic, magnetic, "stripe", or excitonic order across vastly different material classes ranging from cuprate [1][2][3][4][5] and Fe-based high-temperature superconductors [6][7][8] to hydride compounds [9][10][11]. Disentangling the interplay of lattice and electronic degrees of freedom has remained a formidable challenge in many cases.…”
Section: Introductionmentioning
confidence: 99%
“…Different states of electronic quantum matter are often tightly linked to lattice degrees of freedom. Examples include superconductivity, periodic lattice distortions and charge-density waves (CDWs), metal-insulator transitions, and nematic, magnetic, "stripe", or excitonic order across vastly different material classes ranging from cuprate [1][2][3][4][5] and Fe-based high-temperature superconductors [6][7][8] to hydride compounds [9][10][11]. Disentangling the interplay of lattice and electronic degrees of freedom has remained a formidable challenge in many cases.…”
Section: Introductionmentioning
confidence: 99%
“…From deduced (0) values ( Fig. 1 and Table 1), we calculated the Fermi temperature, TF, For H3S phase  = 3.53-4.7, where the lower bound was reported by Kaplan and Imry [34] and in our previous works [35][36][37], and the upper bond was reported by other authors [3,32]. Due to for all three models deduced Tc = 45.9 ± 0.1 K in Table I we show only the Tc/TF ratios.…”
Section: Unannealed H3s (P = 155 Gpa) In Uemura Plotmentioning
confidence: 75%
“…It should be noted, that the discovery of the effect of pressure-induced superconductivity in non-superconducting materials is attributed to Jörg Wittig [8] who converted elemental cerium into superconductor at pressure of P = 5 GPa. During this, more than fifty years, long research journey, pressureinduced superconductivity was found in dozens of non-superconducting elements and compounds (details can be found in recent reviews [3,[9][10][11]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This opens prospects of architecting superconducting nanostructures in order to improve and even tune their characteristics. The most important of them is the critical temperature T c .Main factors that can raise/lower the critical temperature of conventional superconducting materials are well-known since the early years of the BCS theory: modifications of the phonon spectrum [2,3] and disorder effects. [4] Therefore, when first results on the dependence of the critical temperature of nanodimensional superconductors on their geometry appeared, these two factors were immediately employed for explanations; see, for example, refs.…”
mentioning
confidence: 99%